Asuhan Kebidanan Komprehensif pada Ny. A Umur 25 Tahun dengan Anemia di Wilayah Puskesmas Bumiayu Kabupaten Brebes Tahun 2025 (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Background : The Maternal Mortality Rate (MMR) worldwide reaches 183,000 per 100,000 live births (WHO, 2024). In Indonesia, there were 4,305 reported cases (Ministry of Health RI, 2024), while Central Java Province recorded 315 cases (Central Java Health Office, 2024). In Brebes Regency, there were 54 maternal deaths in 2024 (Brebes Health Office, 2024), and in the Bumiayu Public Health Center area, 2 maternal deaths were recorded (Bumiayu PHC Data, 2024). Objective : To analyze, implement, and provide comprehensive midwifery care for Mrs. A, 25 years old, with anemia in the Bumiayu Public Health Center area in 2025, using the Varney midwifery management approach and the SOAP method. Research Methods : This study used a qualitative descriptive design in the form of a case study. Results : Midwifery care during pregnancy for Mrs.A with anemia was carried out bassed on the mother’s needs. During labor, newborn care, postpartum period, and family planning services, no complications were found. Conclusion: The comprehensive midwifery care provided to Mrs. A with anemia was carried out in accordance with the Standard Operating Procedures (SOP), with both the mother and baby in good condition.